Comparison of multiple-locus variable-number tandem-repeat analysis with pulsed-field gel electrophoresis typing of carbapenemases producing Acinetobacter baumannii isolated from burn patients. Issue 2 (March 2016) - Azimi, Leila; Talebi, Malihe; Khodaei, Farzaneh; Najafi, Mohammad; Lari, Abdolaziz Rastegar
Highlights: This study is a molecular epidemiology in carbapenemase producing Acinetobacter baumannii . PFGE and MLVA were used for molecular typing. The discriminatory of PFGE and MLVA were compared in this study. According our results PFGE showed more powerful discriminatory achievement. Abstract: Background: Acinetobacter baumannii is one of the important causes of nosocomial infection especially in burn patients. So, carbapenemase producing strains can make serious therapeutic problems. Molecular epidemiology studies play key role in decreasing the incidence of carbapenemase producing strains. Methods: In this study, 50 carbapenem resistant A. baumannii isolates from burn patients were collected. Antibiotic susceptibility testing and PCR assay was performed for detection of bla VIM, bla IMP, bla OXA-23, bla OXA-48, bla NDM-1, bla SPM-1, bla Oxa -51 and bla KPC genes. Molecular typing for carbapenemase producing strains were performed by PFGE and MLVA. Results: According to the results of antibiotic susceptibility tests all of strains were XDR and 46 (92%) harbored carbapenemase genes. PFGE and MLVA results showed the presence of 11 and 5 dominant clonal types respectively. Conclusion: The results of this study were showed the presence of certain clonal groups in two different wards of hospital indicating the spread of carbapenemase producing A. baumannii . On the other hand, the results showed the more discriminating power for PFGE.